Infliximab for the treatment of plaque psoriasis - Jennifer S Gall (Dove Medical Press, 2008)
Jennifer S Gall, Robert E KalbState University of New York at Buffalo, School of Medicine and Biomedical Sciences, Department of Dermatology, NY, USAAbstract: Infliximab is a monoclonal antibody that targets tumor necrosis factor-α (TNFα). It is used in the treatment of a number of inflammatory disorders including severe plaque psoriasis. TNFα is thought to have a major role in psoriasis by promoting an inflammatory infiltrate into the skin and inducing keratinocyte proliferation and preventing keratinocyte apoptosis, which directly contributes to the characteristic plaque skin lesions. Based on four randomized, placebo-controlled, double-blind clinical trials and nine open-label uncontrolled trials of the use of infliximab in plaque psoriasis, it was found that infliximab is a highly efficacious, rapid, sustainable, and relatively safe therapy. Yet as with any biologic, caution is recommended in its use as infusion reactions, lupus-like syndromes, infections, malignancies including lymphomas, as well as other rare events have been reported.Keywords: infliximab, psoriasis, plaque